Inhibitory effect of chitosan and gelatin on the physical, chemical, organoleptic and mikrobiological quality of keumamah fish - Khafiyya Nida; Uju; Bustami (BIO Web of Conferences)
Keumamah is a traditional fish product made from boiled and sun-dried skipjack, tuna, or mackerel. Keumamah has problems with quality decline and short shelf life. Chitosan, known for its antimicrobial properties, and gelatin, recognized for its ability to form protective layers and preserve food color, are promising natural preservatives for fish products. This study aims to evaluate the effects of chitosan and gelatin on the physical, chemical, organoleptic, and microbiological qualities of keumamah fish. The research utilizes a factorial complete randomized design (CRD) with three treatments: 1% chitosan, 3% gelatin, and a combination of 1% chitosan and 3% gelatin, assessed over storage periods of 0, 7, and 14 days. Key parameters measured include proximate composition, pH, texture, color, peroxide value, water activity (aw), total volatile base (TVB), and total plate count (TPC). The findings indicate that chitosan treatment resulted in the lowest TVB value of 43.57 mg/100g and the lowest peroxide value of 5.11 meq/kg, significantly enhancing the preservation of keumamah. Based on organoleptic tests, gelatin treatment effectively maintained the best texture, while chitosan demonstrated superior preservation of color and aroma due to its antimicrobial properties.